The Coagulation of Politeness and Character in Indonesian Language Learning in the Digital Era - Syahrul Ramadhan; Dewirahmadanirwati Dewirahmadanirwati; Ridha Hasnul Ulya; Norliza Binti Jamaluddin (AL-ISHLAH: Jurnal Pendidikan, 2025)
The digital era has reshaped higher education, particularly in how students communicate both face-to-face and through digital platforms. This study explores linguistic politeness as a key component of student character development and examines its role in shaping communicative behavior in academic settings. A descriptive-analytical approach was used with 30 university students, assessed across five politeness indicators: respectful greetings, polite requests, appropriate language use, avoidance of harsh expressions, and responsiveness. Data were collected through observations of classroom discussions and digital communications (e.g., WhatsApp and E-learning platforms). A frequency-based coding system was applied, with descriptive statistics processed using Microsoft Office tools. The findings revealed high levels of politeness in face-to-face interactions, particularly in greetings and responsiveness. However, digital contexts showed a decline in polite request strategies and a limited awareness of hierarchical norms. For instance, while students consistently used formal greetings in person, these were often omitted in emails. This variation indicates a gap in students’ ability to adapt politeness strategies across contexts. It highlights the importance of integrating digital etiquette into language learning to support ethical and respectful communication. Linguistic politeness should be emphasized in both physical and digital academic environments to cultivate ethical, inclusive, and socially responsible communicators. Interactive learning methods—such as role-play, simulations, and collaborative discussions—are effective in developing these skills and should be embedded in curriculum design.